Azacitidine and donor lymphocytes infusions in acute myeloid leukemia and myelodysplastic syndrome relapsed after allogeneic hematopoietic stem cell transplantation from alternative donors. (June 2022) - Liberatore, Carmine; Stanghellini, Maria Teresa Lupo; Lorentino, Francesca; Vago, Luca; Carrabba, Matteo Giovanni; Greco, Raffaella; Marktel, Sarah; Assanelli, Andrea; Farina, Francesca; Corti, Consuelo; Bernardi, Massimo; Peccatori, Jacopo; et al.
Introduction: Azacitidine (AZA) either single-agent or with donor lymphocytes infusions (DLI) has been used as a salvage treatment for acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) relapsing after allogeneic hematopoietic stem cell transplantation (HSCT). To date, the majority of data come from patients relapsed after HSCT from full-matched donors. Methods: We report a multicenter, collaborative, retrospective analysis of 71 patients with hematologic ( n  = 40, 56%) and molecular relapse ( n  = 31, 44%) of myeloid neoplasms after HSCT from alternative donors (mismatched unrelated, n  = 39, 55%; haploidentical, n  = 29, 41%) consecutively treated at three European centers with AZA ± DLI. Results: Median time from HSCT to relapse was 9 months. Additional DLI were given to 33 patients (46%). After a median of four cycles, overall response rate (ORR) was 49% and complete response (CR) rate was 38%. CR lasted for a median of 17 months (range 5–89 months). Median follow-up in the entire cohort was 11 months (range 1–115 months). Event-free survival (EFS) and overall survival (OS) at 1 year were 26% and 53%, respectively. Treatment of molecular relapse granted higher CR rate (65% versus 15%; p   =  0.0001), 1-year EFS (43% versus 13%; p  = 0.006), and 1-year OS (79% versus 34%; p  < 0.001) compared to hematologic relapses. Addition of DLI resulted in significantly higher responses and longer 1-year EFS and OS (Mantel–Byar test, p  = 0.004 and p   =  0.002, respectively). When applied to our cohort, the APSS-R score confirmed its ability to stratify patients into distinct prognostic groups with significantly different response rates ( p   =  0.0005) and survival ( p  < 0.0001). Treatment was well tolerated, with the incidence of late acute and chronic graft-versus-host disease of 27% and 18%, respectively. Conclusion: AZA ± DLI proved feasible and effective in AML and MDS relapsing after HSCT from alternative donors. Despite modest efficacy among hematologic relapses, pre-emptive treatment with AZA ± DLI fared better in molecular relapse. Additional DLI contributed to improving efficacy and ensuring longer survival.